A novel, cell‐free PCR‐based assay for evaluating the inhibitory activity of antiretroviral compounds against HIV reverse transcriptase. Issue 1 (16th September 2013) - Frezza, Caterina; Balestrieri, Emanuela; Marino‐Merlo, Francesca; Mastino, Antonio; Macchi, Beatrice
Abstract This study describes a novel, PCR‐based assay that evaluates the ability of compounds to inhibit cDNA generation by HIV reverse transcriptase (RT), of both commercial and viral lysate origin, from a known RNA template. The template consisted of RNA from stable transfectants ectopically expressing the US6 gene of herpes simplex virus‐1, coding for glycoprotein D. Controls were carried out to demonstrate that no residual DNA polymerase activity or DNA contamination was responsible for the amplified DNA in the tested, control samples. In this assay, 0.1 μM nevirapine totally inhibited the RT activity of 0.5 U commercial HIV RT, while 10 nM inhibited it by only 10%. Conversely, 10 pM efavirenz completely inhibited 0.5 U HIV RT. Similar results were obtained when a self‐prepared viral lysate was used as a source of HIV RT. A reference commercial kit directly measuring HIV RT activity, without amplification, was less sensitive than the new assay. As a consequence, the HIV RT 50% inhibitory concentration of nevirapine and efavirenz in the newly described assay was 8 and 5 × 103 times lower, respectively, than in the commercial assay. In conclusion, this novel method was sensitive, reproducible, and sufficiently rapid for screening in vitro the functional activity of known or potential antiretroviral compounds against HIV RT. J. Med. Virol. 86:1–7, 2014. © 2013 Wiley Periodicals, Inc.